PERBEDAAN PERUBAHAN WARNA RESIN KOMPOSIT NANOFILLER PADA PERENDAMAN AIR REBUSAN DAUN SIRIH MERAH ( PIPER CROCATUM) DAN OBAT KUMUR NON-ALKOHOL - Aulia, Noor Rizki; Puspitasari, Dewi; Ichrom Nahzi, Muhammad Yanuar (Dentino, 2017)
ABSTRACTBackground: One of resin composite type is nanofiller. Composite resin has tendency to have color change. One factor that can cause color change on the composite resin as mouthwash. Purpose: To determine the difference of color change between nanofiller composite resin that were immersed in decoction water of red bettel leaves (Piper crocatum) and non-alcohol mouthwash. Method: This study was a true experimental research design with control group design pre-test and post-test. It used disk form sample with 10mm diameters and 2mm of thickness. Total samples were 24, divided into 3 treatment groups immersed in decoction water of red bettel leaves (Piper crocatum), non-alcohol mouthwash and sterile aquadest within 24 hours in the incubator with temperature of 37C. Samples were examined by using optical spectrometer (OPT 101 type of photo detector) and microvolt digital. The statistical test was using One-way ANOVA and Post Hoc Bonferroni with <0.05 significance. Result: The result of this study showed significant color change on nanofiller composite resin after immersion in decoction water ofred bettel leaves (Piper crocatum) and non-alcohol mouthwash. Mean value of color change of resin composite immersed in aquadest (0,15Mv), non-alcohol mouthwash (0,24 Mv) and decoction water of red bettel leaves (Piper crocatum) (0,34Mv). Conclusion: There were difference of color change between nanofiller composite resin using the decoction water of red bettel leaves (Piper crocatum) and non-alcohol mouthwash. It showed that composite resin immersed in decoction water of red bettel leaves (Piper crocatum) had higher color change.Keywords : Resin composite nanofiller, color change, mouthwash